Caracteristicas de padroes de drenagem de areas com entalhes erosivos no municipio de Botucatu - SP - Piedade, G. C. R.; Carvalho, W. A.; Garcia, G. J. (My University, 1981)
Descriptive and quantitative characteristics of the drainage pattern of two places very susceptible to erosive process, located in the municipality of Botucatu-SP, were studied through photo-interpretative methods. The analysis and discussion of the obtained results led to the conclusion that the geologic control in the area B, masking the effect of the relief and terrain permeability, increases the drainage density, the length of channels and the angularity of the channels of 3rd and 4th order. -from English summary
Drainage pattern characteristics of areas susceptible to erosive process in the municipality of Botucatu